Biomasa y producción de oxígeno de las especies forestales de la parcela v del arboretum “El Huayo” del Centro de Investigación y Enseñanza Forestal, Puerto Almendra, Loreto 2022 - Ríos Sánchez, Arturo (2024)
A quantitative, basic descriptive study with a non-experimental design was conducted at the "El Huayo" arboretum of CIEFOR. Its main objective was to estimate the biomass and oxygen production (or release) of forest species. The study area is located in a mid-terrace forest, and plot V covers 1.6 hectares. The allometric equation B = 0.0673 * (ρ * DBH) was used to calculate or estimate biomass.2*H)0,976Following the calculations proposed by Chavet et al. (2014), the oxygen production or release was calculated. In the study plot, the estimated biomass is 290.23 t, indicating 181.39 t/ha of aboveground biomass. Therefore, the oxygen production or release in the plot is 1418.13 t, indicating 886.33 t/ha of oxygen released. The statistical data confirm a significant difference between the amount of aboveground biomass and oxygen production. in forest species. Thus, it is concluded that this studied forest demonstrated that its biomass concentration is the best alternative for O production2to the environment, so it could consider economical techniques and at the same time function as sinks.